Migration and Education - Christian Dustmann; Albrecht Glitz (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2011)
Sjaastad (1962) viewed migration in the same way as education: as an investment in the human agent. Migration and education are decisions that are indeed intertwined in many dimensions. Education and skill acquisition play an important role at many stages of an individual's migration. Differential returns to skills in origin- and destination country are a main driver of migration. The economic success of the immigrant in the destination country is to a large extent determined by her educational background, how transferable these skills are to the host country labour market, and how much she invests into further skills after arrival. The desire to acquire skills in the host country that have a high return in the country of origin may also be an important reason for a migration. From an intertemporal point of view, the possibility of a later migration may also affect educational decisions in the home country long before a migration is realised. In addition, the decisions of migrants regarding their own educational investment, and their expectations about future migration plans may also affect the educational attainment of their children. But migration and education are not only related for those who migrate or their descendants. Migrations of some individuals may have consequences for educational decisions of those who do not migrate, both in the home and in the host country. By easing credit constraints through remittances, migration of some may help others to go to school. By changing the skill base of the receiving country, migration may change incentives to invest in certain types of human capital. Migrants and their children may create externalities that influence educational outcomes of non-migrants in the destination country. This chapter will discuss some of the key areas that connect migration and education.
Keywords: 330; Migration; Education; Human Capital; Return Migration; Immigrant Selection; Second-generation